Analisis Implikasi Konsep Sistem Among Dan Trikon Pendidikan Ki Hajar Dewantara di Madrasah Ibtidaiyah - Dianingsig, Dianingsih; Nurkhasanah, Nurkhasanah; Anisah, Retnani; Harni, Harni; Soedjono, Soedjono (Jurnal Inovatif Manajemen Pendidikan Islam, 2024)
This research is motivated by the inconsistency between the curriculum used, namely the independent curriculum, and the practice in the field that is not student-centered. In addition, there is a lack of filters in responding to foreign cultures that enter through technology. The purpose of this study is to analyze the implications of the application of the concept of system among KHD Education in the learning process and the implications of the application of the concept of the theory of KHD Education in the use of technology in learning at MIN 1 Rembang. The research method used is a qualitative descriptive method. In this study, the subjects are teachers at MIN 1 Rembang. Data collection techniques were obtained from documentation, observation, and interviews. Data analysis techniques go through the stages of data collection, data reduction, data presentation, and conclusion. Based on the results of the study, it was obtained that the application of the concept of among system Ki Hajar Dewantara in MIN 1 Rembang was carried out based on the kinship and independence of students which helped students to learn and develop their abilities. Then the application of the concept of Trikon theory is carried out based on three principles, namely continuity, convergence, and concentricity.